The Investment Climate for Female Informal Businesses : A Case Study from Urban and Rural India - Chen, Marty (Washington, DC: World Bank, 2012)
There is worldwide growth in the numbers of people working in the informal economy, either as self-employed in unregistered enterprises or as wage workers in unprotected jobs. Despite earlier predictions to the contrary, it is now widely recognized that the informal economy is a permanent phenomenon, integrally linked to modern capitalist development and to global integration. Although the relationship between the informal economy, the formal economy, and the formal regulatory environment are complex, it is now also widely recognized that informal enterprises, especially those run by women, face different and, arguably, greater constraints to business development than formal enterprises face.